THE ROLE OF PRINCIPAL MANAGERIAL COMPETENCIES IN DEVELOPING ORGANIZATIONAL BEHAVIOR TO REALIZE SUPERIOR EDUCATIONAL QUALITY IN PUBLIC ELEMENTARY SCHOOLS IN SERANG CITY - Dahlia, Ida; Sudadio, Sudadio; Rusdiyani, Isti (International Journal of Multidisciplinary Research and Literature, 2025)
This study aims to analyze the role of principals' managerial competencies in developing organizational behavior to achieve superior educational quality in Public Elementary Schools in Serang City. The research approach uses a qualitative method with interview techniques, observation, and document review, analyzed thematically using NVivo software. The results show that principals' managerial competencies have a significant influence on the formation of positive organizational behavior, particularly in the aspects of collaboration, communication, and teacher work commitment. Principals who have good planning, organizing, and supervisory skills are able to create a conducive learning environment and encourage the improvement of teacher professionalism. This study also found that organizational behavior plays a role as a link between leadership and educational quality, where a healthy work culture can strengthen educator performance. Conditions in Serang City show that variations in quality between schools are influenced by differences in managerial competencies and the effectiveness of school management. This study recommends increasing the capacity of principals through managerial training and strengthening organizational culture so that the quality of elementary education can develop evenly and sustainably